Shortcuts and detours of environmental collective legal mobilizations: the cases of the Atrato River and the Amazon region in Colombia - Ciesielski, Markus; García Carvajal, Carlos Andrés; Vargas Trujillo, Juliette; Justus Liebig University Giessen (My University, 2024)
Colombia's Atrato River and Amazon region were declared legal entities by Colombian judges in 2016 and 2018 respectively. This set the stage for a new era of environmental litigation in Colombia, in which a number of natural entities have been granted this status. In both contrasting cases, non-governmental organizations (NGOs) brought dramatic environmental harms to court through the special acción de tutela procedure, but did not claim a new ecocentric legal status for nature. This article asks how rights were collectively mobilized in the Atrato and Amazon cases and led to ecocentric judgments. Semi-structured interviews were conducted in 2020 with members of NGOs and grassroots organizations involved in these two cases, revealing the emergence of grievance collectives. Through the analysis of these qualitative data, we argue for a perspective that considers the interdependence of legal mobilization and the collective as a social relationship. Collective support led to the choice of an unconventional process. However, this supported the litigation collectives and resulted in ecocentric judgments that generated challenges for the associated collectives in the post-litigation phase. Thus, the analysis of legal mobilization and social relations in the collectives as interdependent improves the understanding of the shortcuts and detours through which complex conflicts have been presented in cases of environmental litigation, and helps to strengthen the scope and concepts of collective legal mobilization.
Keywords: ddc:340